2014
DOI: 10.4028/www.scientific.net/kem.631.113
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of α-Tricalcium Phosphate Powders Surface-Modified with Inositol Phosphate for Cement Fabrication

Abstract: We have previously developed biodegradable β-tricalcium phosphate (β-TCP) cement based on the chelate-setting mechanism of inositol phosphate (IP6). The β-TCP cement powder for the cement fabrication was prepared via a novel powder preparation process, in which the starting β-TCP powders were prepared by simultaneous ball-milling and surface-modification in the IP6 solution. In the present study, the novel powder preparation process was applied to an α-TCP powder, and effect of milling time and beads size for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The 3000 ppm-40 cm 3 -1 mm powder had the second highest SSA. Konishi et al [10] reported that SSA of powder increased when small beads were used in ball-milling, which is agreement with the result of this experiment.…”
Section: Effect Of Ball-milling and Surface Modification Conditions O...supporting
confidence: 91%
“…The 3000 ppm-40 cm 3 -1 mm powder had the second highest SSA. Konishi et al [10] reported that SSA of powder increased when small beads were used in ball-milling, which is agreement with the result of this experiment.…”
Section: Effect Of Ball-milling and Surface Modification Conditions O...supporting
confidence: 91%